Construction and performance of oxidized coal powders based hydrovoltaic devices - Jianhang ZHAO; Zhichao ZUO; Wenwen YU; Yanan YE; Fengbo ZHU; Qiang ZHENG (Meitan xuebao)
The combustion of coal for power generation is accompanied by the production of large amounts of pollutants and greenhouse gases. Therefore, the development of new green power generation methods for coal is of great significance. Hydrovoltaic power generation technology is a novel type of power generation mode that utilizes the interaction between materials and fluid interfaces to generate electrical energy. Increasing interests have been devoted into this area in recent years due to its economical and low-cost merits. This paper presents a novel coal powders (CP) based hydrovoltaic power generator. By regulating the oxygen-containing groups on the surface of the coal powder through oxidation modification, the interactions between coal powder and water molecules can be effectively improved. Combining with a filtration method, modified coal powder/filter paper composite was prepared to assemble a steam-based hydrovoltaic power generator. When the device is immersed in the solution, the water would flow through the bottom of the coal powder/filter paper composite membrane, driven by the effects of evaporation and capillary force. During which, water molecules dissociate continuously within the channels formed by the stacked oxidized coal powders. These negatively charged coal powders lead to the repulsion of anions while attracting cations inside the solution. As a consequence, an electrical double layer is formed on the surface of the coal powder-water flow interfaces. The directed flow of water causes a discrepancy in the migration rate between anions and cations, thereby generating continuous streaming potential. The oxygen functional groups on the surface of the coal powder were characterized using Fourier transform infrared spectrometer and a nanosize particle analyzer. The microstructure of the composite material was observed using scanning electron microscope. The power generation performance of the device was tested using a digital source meter. With the combination of asymmetric electrodes, it can generate a voltage of up to 0.72 V and an output current of 0.4 μA in pure water, with a maximum output power of 29.28 μW/m2. The power generator made from modified coal powder also overcomes the problem of decreased power generation performance in traditional hydrovoltaic generators in high-concentration salt solutions. It can still maintain a stable output voltage of 0.9 V in a 1 mol/L NaCl solution. By connecting multiple hydrovoltaic power generation devices in series, it can directly drive low-power devices, demonstrating its promising potentials.